Design optimization of horizontal pressure vessel. (2020) - Arunkumar, S.; Eshwara Moorthy, P.R.; Karthik, N.
Abstract: The design of horizontal pressure vessel resisting internal pressure with dished heads is available in codes and standards. The safe dimensions of the vessel can be estimated from the same codes and standards. However, the selection of head, locating the nozzles and supports is mostly decided by designer. In the process of selecting the basic pressure vessel parts, it must be ensured that the design can carry the applied load and operate safely and reliably. Thus, it is necessary to find an optimal combination of parts of vessel and locating the nozzles and supports. In this work, a horizontal pressure vessel is designed and optimized using analysis software. The appropriate head shape, optimal location of inlet and outlet nozzles and location of supports is suggested based on the analysis results.